النظر المقاصدي في تفسير العارف بالله أبي الحكم عبد السلام بن برّجان اللخمي الأندلسي ت 536هـ - سعدونى,سهيلة (University of Eloued جامعة الوادي, 2024)
تحفل هذه الدراسة الموسومة بـ: " النظر المقاصديّ في تفسير العارف بالله أبي الحكم عبد السلام بن برّجان اللخمي الأندلسي (ت 536هـ) -الزهراوان نموذجا-" تحفل بالنتاج المقاصديّ المرتبط بآيات وأحكام الاعتقاد على وجه التخصيص عند الفقيه المفسّر الشيخ الواصل ابن برّجان رحمه الله، المبسوط بتصريحه والمفهوم من قبضه وتلويحه ما أسعفتنا الشواهد إلى ذلك سبيلا، توسّلا بتفسيره المسمّى " تنبيه الأفهام إلى تدبّر الكتاب الحكيم وتعرّف الآيات والنّبأ العظيم". حيث وقفنا على الألفاظ والمعاني التي استخدمها في نظره المقاصديّ، بغية بيان التئامها واتّصالها بالخطاب القرآني من جهة وبضوابط الفهم عن الله من جهة أخرى. وقد كشف البحث عن منظومة مقاصديّة متكاملة عند ابن برّجان في تفسيره تقوم على بيان وجوه الحكمة في تدبّر القرآن الكريم ابتداء، وبيان وجوه العلّة في انتخاب المعاني التوسّمية في تفسيره لآيات الاعتقاد انتهاء. Abstract: The study titled "The Purposeful Standpoint in the Interpretation of the Sufi Abu al-Hakam Abdul Salam ibn Barjan al-Lakhmi al-Andalusi (d. 536 AH) - Al-Zahrawan as a Model" is rich with the purposeful outcomes related to the verses and rulings of Islamic belief. These outcomes are expounded explicitly and implicitly as far as the evidence allows, in his interpretation book (Tafseer) named "Tanbih al-Afham ila Tadabbur al-Kitab al-Hakim wa Ta'aruf al-Ayat wa al-Naba' al-Azim." In this study, we examined the words and meanings he used in his purposeful viewpoint to clarify their coherence and connection with the Quranic discourse and the conditions of understanding from Allah. The research revealed a unified purposeful structure in Ibn Barjan's interpretation, which aims to elucidate the aspects of wisdom in reflecting upon the Quran at the outset and to explain the reasons for selecting the intuitive meanings in his interpretation of the verses of belief at the conclusion.
الزهراوان نموذجا
Keywords: ابن برجان; المقاصد; Ibn Barjan; interpretation; viewpoint; purposes; AlZahrawan